The role of nurses and scientist in history of the discovery of parasitic diseases in the world - Reqgi First Trasia (Inspirasi Foundation, 2021)
Introduction: Parasitic disease is still a world health problem. WHO states that parasitic infectious diseases are included in neglected tropical diseases that require large-scale management. Nurses play a major role in the discovery and treatment of parasitic infection patients. However, the role of nurses in the discovery of this parasitic infection is still not well known and discussed. Objective: The aim of this article is to review the role of nurses in history of the discovery parasitic disease in the world. Method: Writing a study of this scientific articles is made using the reading method model or literacy, analyzing and tracing various references. Result: This review found that nursing professional personnel has a great contribution in the invention and nursery of parasitic disease in every patient in the world. Conclusion: As nurses must know how to give the best contribution in every case of infectious disease, especially parasitic disease which is cosmopolite.